A framework for economic evaluation of therapeutic drug monitoring—guided dosing in oncology. Issue 5 (21st September 2021) - Erku, Daniel; Schneider, Jennifer; Scuffham, Paul
Abstract: The standard approach for dose individualization of chemotherapy in the oncology setting has long been based on body surface area (BSA) as a measure of body size. However, for many anticancer drugs, administration of dosages based on BSA may result in some patients receiving supratherapeutic or subtherapeutic concentrations due to substantial interindividual pharmacokinetic variability. Therapeutic drug monitoring (TDM)–guided dosing aims to ensure that the patient's serum drug concentration is in a target range which has been shown to produce optimal clinical outcomes. The management of several malignancies is now moving away from using traditional intravenous chemotherapy to longer‐term treatment with targeted molecular therapies. These targeted anticancer drugs are currently dosed based on a fixed dose for all patients. The pharmacokinetic characteristics of most of these drugs (e.g., tyrosine‐kinase inhibitors) support implementation of individualized dosing via TDM. However, prior to adopting TDM–guided dosing in oncology settings, the economic efficiency and value for money of introducing TDM interventions should be critically and systematically examined along with the impacts on patient care and outcomes. Yet, current evidence in this area is limited, and more generally, there is lack of methodological guidance on how to identify, estimate and value clinical and cost information necessary to conduct economic evaluations of TDM interventions. In this paper, we propose a coherent framework for conducting economic evaluation of TDM interventions in oncology settings and discuss some practical challenges of conducting economic evaluations of TDM.